Adolescent Girls' Awareness towards Reproductive Health in Baghdad City - mohammed, Shatha (Iraqi National Journal of Nursing Specialties, 2013)
Objective: is to determine the level of awareness concerning the reproductive health among adolescent girls inBaghdad City.Methodology: A cross sectional study was performed in order to assess the level of awareness regarding reproductivehealth among 180 adolescent school girls in the age 12-18 years from five secondary schools in Al-Seder Sector inBaghdad city, the data was collected by direct interview using constructed questionnaire to obtain socio-demographiccharacteristics and level of awareness related to reproductive health. The study started from September 2012 toJanuary 2013.Results: the results show that the highest percentage of girls (47.7%) was in age (17-18) year's age, (54.5%) at 4th classsecondary school. The primary school is the educational background of their mothers (40.5%), (41.6%) of therespondents who have large family size. Television and internet were the first source of information (40.9%) ofrespondents. Good awareness regarding menstruation was recorded for (45.5%) of respondents, also good awarenessregarding pubertal body changes among (51.1%) of respondents. Poor awareness recorded among respondentsregarding both gynecological problems (45.6%) and (AIDS) (60.5%).Recommendations: the present study recommends that priority should be given to provide health education toincrease the level of awareness regarding reproductive health for adolescent girls in Baghdad City especially that isrelated to gynecological problems and AIDS.